2013
DOI: 10.1242/jcs.131664
|View full text |Cite
|
Sign up to set email alerts
|

A role for the Golgi matrix protein giantin in ciliogenesis through control of the localization of dynein-2

Abstract: SummaryThe correct formation of primary cilia is central to the development and function of nearly all cells and tissues. Cilia grow from the mother centriole by extension of a microtubule core, the axoneme, which is then surrounded with a specialized ciliary membrane that is continuous with the plasma membrane. Intraflagellar transport moves particles along the length of the axoneme to direct assembly of the cilium and is also required for proper cilia function. The microtubule motor, cytoplasmic dynein-2 med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 51 publications
8
56
0
Order By: Relevance
“…Our hypothesis was that RCAN2 could be suppressing the phenotypes seen following acute loss of giantin in RNAi experiments, namely an increase in cilia length. Consistent with this, we see that reducing the levels of RCAN2 in giantin KO cells recapitulates the longer cilia phenotypes seen on giantin knockdown in WT cells (Asante et al, 2013). Depletion of RCAN2 has no effect on the integrity of the Golgi, nor on targeting of the glycosyltransferase galactosyltransferase T (GalT) (Supplemental Fig.…”
Section: Giantin Ko Cells Show No Gross Defects In Ciliogenesissupporting
confidence: 76%
See 3 more Smart Citations
“…Our hypothesis was that RCAN2 could be suppressing the phenotypes seen following acute loss of giantin in RNAi experiments, namely an increase in cilia length. Consistent with this, we see that reducing the levels of RCAN2 in giantin KO cells recapitulates the longer cilia phenotypes seen on giantin knockdown in WT cells (Asante et al, 2013). Depletion of RCAN2 has no effect on the integrity of the Golgi, nor on targeting of the glycosyltransferase galactosyltransferase T (GalT) (Supplemental Fig.…”
Section: Giantin Ko Cells Show No Gross Defects In Ciliogenesissupporting
confidence: 76%
“…The phenotypes we observe following acute and partial depletion of giantin in mammalian cells (Asante et al, 2013) and zebrafish embryos (Bergen et al, 2017) are not seen following permanent loss of function of giantin. RCAN2 has been characterised as a negative regulator of Nuclear Factor of Activated T-cells (NFAT)-dependent transcriptional activation by calcineurin (Cao et al, 2002;Loh et al, 1996).…”
Section: Cc-by-nc-ndmentioning
confidence: 66%
See 2 more Smart Citations
“…As a second approach, we analyzed the distribution of the recycling endosomal marker rab11a (Ullrich et al, 1996). Rab11a is mainly expressed at the apical aspect of zebrafish hair cells (Clark et al, 2011), and its involvement in ciliogenesis has been demonstrated (Westlake et al, 2011;Asante et al, 2013). Fig.…”
Section: Clarin-1 Involvement In Vesicle Recyclingmentioning
confidence: 99%